2020
DOI: 10.1101/2020.09.21.306761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Integrated Multimodal Model of Alcohol Use Disorder Generated by Data-Driven Causal Discovery Analysis

Abstract: Objective: Alcohol use disorder (AUD) has high prevalence and adverse societal impacts, but our understanding of the factors driving AUD is hampered by a lack of studies that describe the complex multifactorial mechanisms driving AUD. Methods: We used Causal Discovery Analysis (CDA) with data from the Human Connectome Project (HCP; n = 926 [54% female], 22% AUD [37% female]). Our outcome variable was number of AUD symptoms. We applied exploratory factor analysis (EFA) to parse phenotypic measures into underly… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 94 publications
3
13
0
Order By: Relevance
“…These results converge with previous studies and systematic reviews that have demonstrated that CUD is characterized by changes in the brain's memory system (32,33,78), the reward and salience networks (32,34), and the occipital lobe (79,80). These results also demonstrate changes in the brain's reward/approach-related system, a domain that was not captured well by the behavioral assessments or neuroimaging tasks used in this study (see Rawls and colleagues [11] for a more in depth discussion). Thus, the current evidence supports the triadic models of cannabis addiction by indicating changes in the brain's reward/approach system, deficits in executive function, specifically in working memory function and verbal IQ, and a role of negative affect, specifically of externalizing symptoms and aggression.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results converge with previous studies and systematic reviews that have demonstrated that CUD is characterized by changes in the brain's memory system (32,33,78), the reward and salience networks (32,34), and the occipital lobe (79,80). These results also demonstrate changes in the brain's reward/approach-related system, a domain that was not captured well by the behavioral assessments or neuroimaging tasks used in this study (see Rawls and colleagues [11] for a more in depth discussion). Thus, the current evidence supports the triadic models of cannabis addiction by indicating changes in the brain's reward/approach system, deficits in executive function, specifically in working memory function and verbal IQ, and a role of negative affect, specifically of externalizing symptoms and aggression.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the current results confirm the importance of multi-domain investigations into the factors underlying drug addiction, as in our previous empirical investigation of multi-domain factors in substance use disorders (11).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results suggest interventions that enhance efficiency in an individual’s use of cortical resources for cognitive control and reinforcement processing (i.e., identification of salient stimuli and shifting of attention toward or away from such stimuli) may significantly impact their engagement in hazardous alcohol use. Importantly, previous research by our group has shown that PFC function might have a downstream causal impact on severity of alcohol use disorder (Rawls et al, 2021), suggesting that interventions focused on PFC function could improve cognitive function in individuals with problematic alcohol use.…”
Section: Discussionmentioning
confidence: 90%
“…The discovered hub role of the frontoparietal network in the causal human connectome is especially attractive, as brain-based therapies for psychiatric conditions typically impact or directly stimulate nodes in the frontoparietal network (Belsher et al, 2021; Ferrarelli and Phillips, 2021; Fitzgerald, 2021; Song et al, 2019; Voigt et al, 2021; Zhang et al, 2021; Zilverstand et al, 2017, 2016). Previously, we even demonstrated that connectivity in the frontoparietal network has downstream causal effects on the severity of alcohol use disorder (Rawls et al, 2021). As it is applied on a single-subject basis, the GANGO method could potentially even enable individualized causal connectivity-based neuromodulation targeting.…”
Section: Discussionmentioning
confidence: 98%